Pattern of Decision-Making Evaluation in Urban Regeneration - jalal haghighi; saideh Zahra sadat zarabadi; mostafa behzadfar; mojtaba rafiyan (تحقیقات کاربردی علوم جغرافیایی)
Evaluation is one of the most important necessities in the process of urban regeneration, which leads to the optimal decision to solve the problem of urban inefficiency. Evaluating decisions in the urban regeneration process, given its complexity, ambiguity and uncertainty, is a critical issue that requires identifying the criteria that affect its realization and using fuzzy decision-making methods. The purpose of this study is to introduce a fuzzy Delphi method based on qualitative reasoning to identify and localize the criteria affecting urban regeneration. The research method is a combination of quantitative and qualitative methods. The present study is applied in terms of developmental goal and descriptive-analytical in terms of researcher action. The content analysis method was used to develop the conceptual model of the research and the fuzzy inference system (FIS) and Matlab and SPSS software were used to analyze the components and criteria of urban regeneration. To obtain the required data for the research, open and closed questionnaires were distributed among experts and the expert group. Then, the obtained data were entered into the fuzzy inference system and their output was considered as research findings. According to the results of the study, 18 criteria were identified to evaluate the regeneration policy. These criteria were reduced to 12 criteria in the final selection stage, which was done by Delphi interview method. The results show that the most important and insignificant components of urban regeneration in Qom are economic, functional, physical, managerial, social and environmental components, respectively. General Transportation and Access to Urban Management Safety and Health, Housing and Infrastructure.